An evaluation of the robustness of organ-at-risk recommendations made by GEC/ESTRO according to interobserver variability: a single-center experience - Chicas-Sett, Rodolfo; Celada-Alvarez, Francisco; Roldán, Susana; Torregrosa, Asunción; Betancourt, Jesus; Bautista-Ballesteros, Juan; Farga, Dolores; Ibañez, Blanca; Tormo, Alejandro; Perez-Calatayud, Jose (Journal of Contemporary Brachytherapy, 2016)
Purpose : Groupe Européen de Curiethérapie (GEC) and European Society for Radiotherapy & Oncology (ESTRO) has proposed a rectal dose constraint of the most exposed 2-cc volume (D 2cc of ≤ 75 Gy EQD 2α/β = 3) during external- beam plus high-dose-rate brachytherapy (HDR-BT) in localized prostate cancer patients. This study aimed to evaluate D 2cc for rectal contouring via interobserver variability. Material and methods: Four blinded observers contoured rectums of 5 patients. Rectal contouring anatomical limits were determined through previous consensus. Dose-volume histogram (DVH) dosimetric parameters (D 0.1cc , D 1cc , and D 2cc ) were analyzed according to GEC/ESTRO recommendations and subjected to intra- and interobserver comparisons. Latter comparisons involved coefficients of variation. For each parameter, the mean, standard deviation (SD), and range were evaluated. The effect of interobserver variation on total dose was analyzed by estimating the biologically equivalent rectal dose (EQD 2α/β = 3). Results : Interobserver coefficients of variation for D 0.1cc , D 1cc , and D 2cc were 5.7%, 4.5%, and 4%, respectively. The highest interobserver rectal delineation variation yielded a rectal dose difference up to 5.8 Gy EQD2. Estimated intraobserver variation for the reported D 2cc was 5.5% in the worst-case scenario (non-significant). Conclusions : We observed acceptable interobserver variability in EQD2 for D 2cc , with strong impacts on clinical threshold levels (D 2cc ≤ 75 Gy EQD2) in some cases. This small, single-center analysis will be extended in a multicenter study.